The Political Economy of Distress in East Asian Financial Institutions - Bongini, Paola (World Bank, Washington, DC, 2015)
Politics and regulatory capture can play an important role in financial institutions distress. East Asia's financial crisis featured many distressed and closed financial intermediaries in an environment with many links between government, politicians, supervisors, and financial institutions. This makes the East Asian financial crisis a good event for studying how such connections affect the resolution of financial institutions distress. The authors investigate distress and closure decisions for 186 banks and 97 non-bank financial institutions in Indonesia, the Republic of Korea, Malaysia, the Philippines, and Thailand. They find that after July 1997, 42 percent of the institutions experienced distress (were closed, merged, or re-capitalized, or had their operations temporarily suspended). By July 1999, 13 percent of all institutions in existence in July 1997 had been closed. Using financial data for 1996, the authors find that: 1) Traditional CAMEL-type variables - returns on assets, loan growth, and the ratio of loan loss reserves to capital, of net interest income to total income, and of loans to borrowings - help predict subsequent distress and closure. 2) None of the foreign-controlled institutions were closed, and foreign portfolio ownership lowered an institutions probability of distress. 3) Connections - with industrial groups of influential families - increased the probability of distress, suggesting that supervisors had granted forbearance from regulations. Connections also made closure more, not less, likely - suggesting that the closure processes themselves were transparent. 4) But larger institutions, although more likely to be distressed, were less likely to be closed, while (smaller) non-bank financial institutions were more likely to be closed. This suggests a too big to fail policy. 5) These policies, together with the fact that resolution processes were late and not necessarily comprehensive, may have added to the overall uncertainty and loss of confidence in the East Asian countries, aggravating the financial crisis.